The Lincolns : a scrapbook look at Abraham and Mary - Fleming, Candace (New York : Schwartz & Wade Books, 2008)
A dual biography of Abraham Lincoln and his wife, Mary, using photographs, letters, engravings, and cartoons to look at their childhoods, courtship, marriage, children, and other joys and traumas of their years together, including their deaths.
Backwoods boy -- Bluegrass girl -- The happiest stages of life -- Tumultuous times -- And the war came: Washington, 1861 -- This awful burden: Washington, 1862-63 -- With charity for all: Washington, 1864-65 -- Blind from weeping.
Includes bibliographical references (p. 158-176) and index.
School Library Journal starred.
Wilson's Junior High School.
Wilson's Senior High School.
Book Links (A.L.A.), January 2009.
Booklist starred, September 2008.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Mary Todd, -- 1818-1882 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Lincoln, Mary Todd, -- 1818-1882.; Lincoln, Abraham, -- 1809-1865.; Lincoln, Mary Todd, -- 1818-1882.; Married people -- United States -- Biography -- Juvenile literature; Presidents' spouses -- United States -- Biography -- Juvenile literature; Presidents' spouses -- United States -- History -- 19th century -- Sources -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Presidents -- United States -- History -- 19th century -- Sources -- Juvenile literature; First ladies; Married people; Presidents; Presidents' spouses -- History -- 19th century -- Sources; Presidents -- History -- 19th century -- Sources; Married people -- United States -- Biography; Presidents' spouses -- United States -- Biography; Presidents' spouses -- United States -- History -- Sources; Presidents -- United States -- Biography; Presidents -- United States -- History -- Sources; United States -- History -- Civil War, 1861-1865 -- Sources -- Juvenile literature; Washington (D.C.) -- History -- Civil War, 1861-1865 -- Sources -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Sources; Washington (D.C.) -- History -- Civil War, 1861-1865 -- Sources; United States -- History -- 1861-1865, Civil War -- Sources; Washington (D.C.) -- History -- Sources